Pengaruh kepemimpinan transformasional terhadap kinerja perawat di RSUD Suradadi Kabupaten Tegal - Riyanto, Agus; Pujiyanto, Tri Ismu; Dedi, Blacius (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: Transformational leadership is known as a leadership approach capable of motivating and inspiring subordinates to achieve higher performance through empowerment and a shared vision. This study aims to examine the effect of transformational leadership intervention on improving nurses' performance. Methods: The research design used is quantitative with a quasi-experimental approach, employing a pretest-posttest with control group design. The research sample consisted of nurses participating in the transformational leadership intervention program, with 15 respondents in the intervention group and 15 respondents in the control group over a specific period. Data collection was carried out by measuring performance before and after the intervention using a nurse performance questionnaire, and the data were then analyzed using univariate tests for respondent characteristics, followed by bivariate tests using the non-parametric Wilcoxon test and the Mann-Whitney U test. Results:The analysis results showed a p-value of 0.001 < 0.05, indicating that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. The findings reveal a significant effect of transformational leadership intervention on improving nurses' performance. Conclusion: The conclusion of this study suggests that the implementation of transformational leadership can serve as an effective managerial strategy to enhance nurses' performance. The practical implication of this research recommends transformational leadership training and development for nurse managers or head nurses in healthcare facilities.